High expression of neutrophil and monocyte CD64 with simultaneous lack of upregulation of adhesion receptors CD11b, CD162, CD15, CD65 on neutrophils in severe COVID-19. (July 2021) - Karawajczyk, Malgorzata; Douhan Håkansson, Lena; Lipcsey, Miklos; Hultström, Michael; Pauksens, Karlis; Frithiof, Robert; Larsson, Anders
Background and Aims: The pronounced neutrophilia observed in patients with coronavirus disease 2019 (COVID-19) infections suggests a role for these leukocytes in the pathology of the disease. Monocyte and neutrophil expression of CD64 and CD11b have been reported as early biomarkers to detect infections. The aim of this study was to study the expression of receptors for IgG (CD64) and adhesion molecules (CD11b, CD15s, CD65, CD162, CD66b) on neutrophils and monocytes in patients with severe COVID-19 after admission to an intensive care unit (ICU). Methods: The expression of receptors was analyzed using flow cytometry. EDTA blood from 23 patients with confirmed COVID-19 infection was sampled within 48 h of admission to the ICU. Leukocytes were labeled with antibodies to CD11b, CD15s, CD65s, CD162, CD64, and CD66b. Expression of receptors was reported as mean fluorescence intensity (MFI) or the percentage of cells expressing receptors. Results: Results are presented as comparison of COVID-19 patients with the healthy group and the receptor expression as MFI. Neutrophil receptors CD64 (2.5 versus 0.5) and CD66b (44.5 versus 34) were increased and CD15 decreased (21.6 versus 28.3) when CD65 (6.6 versus 4.4), CD162 (21.3 versus 21.1) and CD11b (10.5 versus 12) were in the same range. Monocytes receptors CD64 (30.5 versus 16.6), CD11b (18.7 versus 9.8), and CD162 (38.6 versus 36.5) were increased and CD15 decreased (10.3 versus 17.9); CD65 were in the same range (2.3 versus 1.96). Conclusion: Monocytes and neutrophils are activated during severe COVID-19 infection as shown by strong upregulation of CD64. High monocyte and neutrophil CD64 can be an indicator of a severe form of COVID19. The adhesion molecules (CD11b, CD162, CD65, and CD15) are not upregulated on otherwise activated neutrophils, which might lead to relative impairment of tissue migration. Low adhesion profile of neutrophils suggests immune dysfunction of neutrophils. Monocytes maintain upregulation of some adhesion molecules (CD11b, CD162) suggesting the persistence of an increased ability to migrate into tissues, even during a severe stage of COVID-19. Future research should focus on CD64 and CD11b kinetics in the context of prognosis.